Ecclesiastes and Song of Songs - Curtis, Edward M. (Grand Rapids, Michigan : Baker Books, 2013)
"The Teach the Text Commentary Series gives pastors the best of biblical scholarship and presents the information needed to move seamlessly from the meaning of the text to its effective communication. By keeping the discussion in each carefully selected preaching unit to six pages of focused commentary, the volumes allow pastors to quickly grasp the most important information. Each unit of the commentary includes the big idea and key themes of the passage; sections dedicated to understanding, teaching, and illustrating the text; and full-color images. How do we find meaning in life when it seems futile and meaningless? Ecclesiastes takes readers on a journey pondering this timeless question, and this commentary helps set the book within a biblical worldview in order to help teachers communicate and apply the profound truths of Ecclesiastes today. Song of Songs is full of evocative poetry, but centuries of interpretation have produced little consensus about how this unique book should be understood. Edward M. Curtis lays out the key themes of the book and provides carefully organized commentary for interpreting, teaching, and illustrating this book" -- Publisher description.
Introduction to Song of Songs -- the greatest song: a song about love -- Song of Songs 1:1-2:7 -- passion, praise, and delight -- Song of Songs 2:8-3:5 -- my beloved is mine, and I am his -- Additional insights -- boundaries as part of God's order -- Song of Songs 3:6-5:1 -- you are beautiful, my love: delight and consummation -- Additional insights -- a wedding describe -- beyond physical beauty -- Song of Songs 5:2-6:3 -- what is so special about your beloved? -- Song of Songs 6:4-7:13 -- the spectacular delights of love -- Additional insights -- relationships that reflect Yahweh's order: moving beyond Song of Songs -- Song of Songs 8:1-14 -- the awesome power of love -- Additional insights -- love and the choices we make.
Includes bibliographical references (pages 170-173) and index.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries